Prokaryotic plankton respiration, growth and abundance in the Arctic Ocean 2021 - Wikner, Johan; Pinhassi, Jarone; Verma, Ashish; Amnebrink, Dennis (Umeå University, 2024)
The dataset consists of results from measurements of prokaryotic (Bacteria and Archaea) plankton respiration, growth, and abundance in the Arctic Ocean surface (0-500 m) in 2021. Data was collected during the Synoptic Arctic Survey expedition with the Swedish research icebreaker Oden between July 25 and September 20, 2021.
Samples were collected primarily with Niskin-bottles on a rosette-sampler equipped with a CTD probe. Some samples were also taken in the boundary layer between ice and seawater with a Ruttner sampler after a hole to the water surface was drilled.
Process speeds were measured on board within an hour of sampling in a cool laboratory with a temperature of 7°C. Plankton respiration was measured by oxygen optodes in eight simultaneous samples incubated at in situ temperature. For the PROMAC project, all samples were pre-filtered with 1.2 μm filters to specifically measure prokaryotic respiration. Growth of the prokaryotic community was measured by uptake of the DNA base thymidine labeled with tritium incubated at in situ temperature. The presence of prokaryotes was measured by epifluorescence microscopy after labeling with the dye acridine orange. Cell morphology and interactions were also studied via scanning electron microscopy in samples preserved with glutaraldehyde. In the filtered samples, the presence of different prokaryotic taxa was determined by sequencing the 16S RNA gene. In addition, expression of genes from isolated mRNA was measured. For metagenomics and transcriptomics from unfiltered samples, please refer to the OMICS project from the same expedition.
The main projects (“SASIce24h” and “SAS”) aim to contribute knowledge about prokaryotic plankton respiration, growth rate and total biomass to better understand the turnover of carbon in the Arctic Ocean and its regulation. The results from the expedition will also provide a basis for comparison with similar studies in the future to follow climate change. The spatial coverage will increase the understanding of how processes vary in different parts of the ocean. Simultaneous measurements in other parts of the Arctic Ocean by other countries will contribute to a more comprehensive picture. The “PROMAC” project studies the maintenance respiration of prokaryotic plankton and what activities are included there. The temperature sensitivity of plankton respiration is investigated in the “RespirationQ10”-project. Determination of the conversion factor from thymidine uptake to cell growth is carried out in the subproject "TCF". Whether enough of the trace element thymidine was added was investigated in the sub-project ”Isotope dilution”. First results will be published during 2024.

Data setet utgörs av resultat från mätningar av prokaryota (Bakterier och Arkéer) planktons respiration, tillväxt och förekomst i Arktiska oceanens ytksikt (0-500 m) 2021. Data insamlades under expeditionen Synoptic Arctic Survey med den svenska forskningsisbrytaren Oden mellan 25 juli och 20 september 2021.
Prover insamlades främst med Niskin-flaskor på en rosett-hämtare utrustad med en CTD-sond. Några prover togs också i gränsskiktet mellan is och havsvatten med Ruttner hämtare efter att ett hål till vattenytan borrats.
Processhastigheter mättes ombord inom någon timme från provtagning i ett svalt laboratorium med en temperatur på 7 °C. Planktonrespiration mättes med syre-optoder i åtta samtidiga prover inkuberade vid in situ-temperatur. För PROMAC-projektet förfiltrerade samtliga prover med 1,2 µm filter för att specifikt mäta prokaryot respiration. Tillväxt hos det prokaryota samhället mättes med upptag av DNA-basen tymidin märkt med tritium inkuberade vid in situ-temperatur. Förekomst av prokaryoter mättes med epifluorescens-mikroskopi efter inmärkning med färgämnet akridinorange. Cellmorfologi och -interaktioner studerades också via skannande elektronmikroskopi i prover konserverade med glutaraldehyd. I de filtrerade proverna bestämdes förekomsten av olika prokaryota taxa med sekvensning av 16S-RNA genen. Dessutom mättes uttryck av gener från isolerat mRNA. För metagenomik och transkriptomik från ofiltrerade prover hänvisas till OMICS-projektet från samma expedition.
Huvudprojekten (”SASIce24h” och ”SAS”) har som syfte att bidra med kunskap om prokaryota planktons respiration, tillväxthastighet och totalbiomassa i syfte att bättre förstå omsättningen av kol i Arktiska oceanen och regleringen av den. Resultaten från expeditionen ska ge underlag för jämförelse med liknande studier i framtiden för att följa klimatförändringar. Den rumsliga täckningen ska öka förståelsen av hur processerna varierar i olika delar av oceanen. Samtidiga mätningar i andra delar av andra länderav Arktiska oceanen ska bidra till en mer heltäckande bild. I projektet ”PROMAC” studeras underhållsrespirationen hos prokaryota plankton och vilka aktiviteter som ingår där. Temperaturkänsligheten hos planktonrespiration undersöks i projektet ”RespirationQ10”. Bestämning av konversionsfaktorn från tymidinupptag till celltillväxt utfördes i delprojektet ”TCF”. Om tillräcklig mängd av spårämnet tymidin tillsattes undersöktes i delprojektet ”Isotope dilution”. Resultaten ska börja publiceras under 2024.
Prokaryota planktons respiration, tillväxt och förekomst i Arktiska oceanen 2021
Keywords: procaryote; Procaryotæ (prokaryota organismer); Habitats and biotopes; Naturtyper och biotoper; Sea regions; Havsområden; arctic research; arktisk forskning; marine ecology; marinekologi; arctic region; arktiska regionen; microbial ecology; mikrobekologi; prokaryotes; archaea; bacteria cavalier-smith, 2002; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Microbiology; Mikrobiologi; Ecology; Ekologi; Biota; Biologi och ekologi; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Environment; Miljö